Whole genome sequencing analysis of SARS-CoV-2 Omicron variant isolated ‎from Egypt‎ - Hanaa Ahmed; Mohamed Seadawy; Mohamed Abdel-Razik; Ahmed Gad; Mervet Hassan (Microbes and Infectious Diseases)
Background:  The omicron variants have been classified as variants of concern by the world health organization due to their initial emergence with a notable mutations that affect on the transmissibility, immune escape and virulence of the SARS-CoV-2 virus. We conducted a cross-sectional analysis study to detect the most common strain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Egypt during the 4th wave of the COVID-19 pandemic and used the next genaration sequencing to characterize the SARS CoV-2 omicron variant genome and find the significant mutation influencing the virus's virulence, immune evasion, and transmissibility. Methods: This study started during the 4th wave of the COVID-19 pandemic by collecting nasopharyngeal swabs (n = 39) from individuals having COVID-19 symptoms. SARS-CoV-2 was molecularly identified using reverse transcription PCR (RT-PCR). For every sample, whole genome sequencing (WGS) was carried out using next generation sequencing Illumina Iseq100 system. Clade assignment, Pangolin lineages, phylogenetic placement, and mutation calling were all carried out using Nextclade tool V3.4.0, Coronavirus Typing Tool V 1.25 and CoVsurver mutation application‎. Result: Sequencing data analysis proved that all the involved samples in the study belong to the Omicron variant with different clade and Pangolin lineage, the most common strain in Egypt during the 4th wave of the COVID-19 pandemic was Omicron clade 22B and BA.5.2 Pango lineage. Mutation analysis showed that the S gene of the omicron variant accumulated with significant mutations that affect viral immune escape. Conclusion: The omicron variant in Egypt during the 4th wave of the pandemic showed a high ability to escape from the immune system because of newly mutation on the antibodies recognized sites of the S gene, so it is very important to perform continuous monitoring for omicron genome mutations using next-generation sequencing to help the scientific community in the development of appropriate vaccine for this variant.